2001
DOI: 10.1006/dbio.2001.0379
|View full text |Cite
|
Sign up to set email alerts
|

Duplicate mitf Genes in Zebrafish: Complementary Expression and Conservation of Melanogenic Potential

Abstract: Mutations in the zebrafish nacre/mitfa gene, expressed in all embryonic melanogenic cells, perturb only neural crest melanocytes, suggesting redundancy of mitfa with another gene in the zebrafish retinal pigment epithelium (RPE). Here, we describe a second zebrafish mitf gene, mitfb, which may fulfill this role. The proteins encoded by the two zebrafish mitf genes appear homologous to distinct isoforms generated by alternately spliced mRNAs of the single mammalian Mitf gene, suggesting specialization of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
176
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(183 citation statements)
references
References 57 publications
7
176
0
Order By: Relevance
“…In this case, both copies are preserved, since the presence of both is necessary to perform the original function of the ancestral single-copy gene. In teleosts, the evolution of numerous gene duplicates is consistent with the subfunctionalization model (eg Lister et al, 2001;Serluca et al, 2001;Altschmied et al, 2002;McClintock et al, 2002;Cresko et al, 2003;Yu et al, 2003;Amores et al, 2004). For example, mammals and birds have a unique microphthalmia-associated transcription factor gene mitf, from which different isoforms are expressed through the use of different promoter sequences and alternative exons.…”
Section: Fish-specific Gene and Genome Duplicationsmentioning
confidence: 72%
See 2 more Smart Citations
“…In this case, both copies are preserved, since the presence of both is necessary to perform the original function of the ancestral single-copy gene. In teleosts, the evolution of numerous gene duplicates is consistent with the subfunctionalization model (eg Lister et al, 2001;Serluca et al, 2001;Altschmied et al, 2002;McClintock et al, 2002;Cresko et al, 2003;Yu et al, 2003;Amores et al, 2004). For example, mammals and birds have a unique microphthalmia-associated transcription factor gene mitf, from which different isoforms are expressed through the use of different promoter sequences and alternative exons.…”
Section: Fish-specific Gene and Genome Duplicationsmentioning
confidence: 72%
“…Hence, the two mitf genes are required together to perform the functions of the unique mitf gene in mammals and birds. This partitioning of functions is associated with the degeneration of isoform-specific exons and regulatory sequences (Lister et al, 2001;Altschmied et al, 2002).…”
Section: Fish-specific Gene and Genome Duplicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two hours post fertilization, invagination of the central portions of this eye-mass and formation of the optic lumen contribute to the formation of an optic cup (Table I; Dowling, 1994, 1999)). The inner layer continues to proliferate and produces the neural retina, whereas the outer layer gives rise to the retinal pigment epithelium (RPE), likely through the action of mitf expression (Lister et al, 2001). The positioning of the optic stalk is regulated by the expression of the Pax2 and Pax6 genes (Macdonald et al, 1995).…”
Section: Eye Developmentmentioning
confidence: 99%
“…In this context, nonfunctionalization, subfunction partitioning, and neofunctionalization, occurring independently in separate lineages, could lead to different functions, differential subfunction partitioning, relaxation of pleiotropic constraints, and speciation (Lynch and Force, 2000;Taylor et al, 2001;Postlethwait et al, 2004;Force et al, 2004Force et al, , 2005. Empirical studies have shown great support for the molecular mechanisms of the subfunctionalization model (Lister et al, 2001;Altschmied et al, 2002;Cresko et al, 2003;Liu et al, 2005).…”
mentioning
confidence: 99%